Into the gauntlet [compact disc, unabridged] - Haddix, Margaret Peterson (39 clues, 2010)
After crossing five continents and solving some of history's most perplexing mysteries, Amy and Dan Cahill are nearing the end of their adventure. As the final clue promises to reveal the truth about the Cahill family's awesome power, Amy and Dan must successfully complete a challenge that their ancestors have failed for nearly 500 years.